Increase Human Metapneumovirus Mediated Morbidity following Pandemic Influenza Infection - Regev, Liora; Meningher, Tal; Hindiyeh, Musa; Mendelson, Ella; Mandelboim, Michal (PLOS ONE, 2012)
Human metapneumovirus (hMPV) is a recently discovered respiratory pathogen, infecting mainly young children. The infected patients suffer from influenza like symptoms (ILS). In Israel the virus is mainly circulating in February to March. Here we report on an increased rate of hMPV infection in the winter season of 2009–10. The 2009–10 infection had several unique characteristics when compared to previous seasons; it started around January and a large number of infants were infected by the virus. Genetic analysis based on the viral L and F genes of hMPV showed that only subtypes A2 and B2 circulated in Israel. Additionally, we have identified a novel variant of hMPV within subgroup A2b, which subdivide it into A2b1 and A2b2. Finally, we showed that the hMPV infection was detected in the country soon after the infection with the pandemic influenza virus had declined, that infection with the pandemic influenza virus was dominant and that it interfered with the infection of other respiratory viruses. Thus, we suggest that the unusual increase in hMPV infection observed in 2009–10 was due to the appearance of the pandemic influenza virus in the winter season prior to 2009–10.